The Embryonic Develompent and Hatching Rate of Cantang Grouper (Epinephelus fuscoguttatus, Forskall 1775 x Epinephelus lanceolatus, Bloch 1790) - Albet Surya Kembara; Putri Desi Wulan Sari (Kontribusia : Research Dissemination for Community Development, 2020)
Cantang grouper is a grouper species produced from the hybridization of Kertang grouper and Tiger grouper. The hybridization,besides increasing species diversification, also has the prospect of cultivation that has the opportunity to increase fishery production in the future. The technique of maintaining grouper larvae needs to be known to be able to increase the production value of the grouper larvae and create technological opportunities in the production process. The embryonic development phase of cantang grouper egg consists of multicellular phase, blastula, gastrula, separation of the tail from the egg sac, the movement of embryo, internal organ formation and the hatching eggs. During the two months maintenance period, the Hatching Rate (HR) larvae were found to be 80%.